Strategi Pengembangan UMKM Makanan dan Minuman di Kelurahan Tamansari Kota Bandung - Ahmad Kholik; Dewi Rahmi (Jurnal Riset Ilmu Ekonomi dan Bisnis, 2023)
Micro, small and medium enterprises (MSMEs) have an important role in the development of the Indonesian economy, especially in the food and beverage sector which is growing rapidly. However, MSMEs in Tamansari Village, Bandung City face challenges such as capital, marketing, business legality and substandard human resources. This research uses quantitative descriptive methods and SWOT analysis to discuss strategies for developing MSMEs in the food and beverage sector in the region. Research findings show four alternative strategies that can be used by MSMEs in Tamansari village. SO strategy (strengths and opportunities), ST strategy (strengths and threats), WO strategy (weaknesses and opportunities), and WT strategy (weaknesses and threats). By taking a sample of 91 MSME respondents and 52 consumers, this research provides a strategic basis for responding to the challenges faced by economic actors. The implementation of this strategy is expected to increase the competitiveness of MSMEs in the food and beverage sector, support regional economic growth, and strengthen the contribution of the MSME sector to the national economy. Usaha mikro, kecil dan menengah (UMKM) mempunyai peranan penting dalam pembangunan perekonomian Indonesia, khususnya pada sektor makanan dan minuman yang berkembang pesat. Meski demikian, UMKM di Desa Tamansari Kota Bandung menghadapi tantangan seperti permodalan, pemasaran, legalitas usaha, dan sumber daya manusia yang kurang lancar. Penelitian ini menggunakan metode deskriptif kuantitatif dan analisis SWOT untuk membahas strategi pengembangan UMKM sektor makanan dan minuman di daerah. Temuan penelitian menunjukkan empat alternatif strategi yang dapat digunakan oleh UMKM di desa Tamansari. Strategi SO (strengths and opportunities), strategi ST (strength and threats), strategi WO (Weaknes and opportunity), dan strategi WT (weaknes and threats). Dengan menyertakan sampel sebanyak 91 responden UMKM dan 52 konsumen, penelitian ini memberikan landasan strategis untuk menjawab tantangan yang dihadapi pelaku ekonomi. Penerapan strategi tersebut diharapkan dapat meningkatkan daya saing UMKM sektor makanan dan minuman, mendukung pertumbuhan perekonomian daerah, dan memperkuat kontribusi sektor UMKM terhadap perekonomian nasional.